Laparoscopic total mesorectal excision with urogenital fascia preservation for mid-low rectal cancer: Anatomical basis and clinical effect - Experimental research. (March 2022) - Liu, Hailong; Chang, Yi; Li, Ajian; Wang, Wenchao; Lv, Liang; Peng, Jian; Pan, Zhihui; Jiang, Huihong; Lin, Moubin
Abstract: Background: Total mesorectal excision (TME) is conventionally performed according to Heald's principles through the so-called 'holy plane', between the visceral and parietal fasciae. However, urinary and sexual dysfunctions remain frequent postoperative complications. We proposed to preserve urogenital fascia (UGF) in TME, and this study aimed to clarify the anatomical basis of this technique and evaluate its efficacy and safety. Materials and methods: Cadaveric dissection was performed on 26 pelvises, and laparoscopic TME with UGF preservation was performed in 212 patients with mid-low rectal cancer. The fasciae and spaces related to TME were observed and described, and the clinical effect of UGF-preserving TME was analyzed. Results: In the 26 cadavers, fascia propria of the rectum (FPR) presents as a fibrous capsule enveloping the mesorectum. UGF extends postero-laterally to the rectum, enveloping the hypogastric nerves and ureters. We demonstrated that the visceral fascia is actually the UGF, and FPR and visceral fascia (i.e. UGF) are two independent layers of fascia. Thus, FPR, UGF and parietal fascia form two avascular spaces behind the rectum. The plane ventral to the UGF is the real 'holy plane' for TME, rather than that dorsal to the UGF as is traditionally thought. Laparoscopic TME with UGF preservation was successfully performed in all 212 patients, with low perioperative complications (10.8%) and a low 3-year local recurrence rate (4.2%). Furthermore, the incidences of urinary and sexual dysfunctions at postoperative 6 months were only 6.1% and 10.8%, respectively. Conclusion: The avascular plane between the FPR and UGF (i.e. visceral fascia) is the real 'holy plane'. Laparoscopic TME with UGF preservation is a feasible radical surgery for mid-low rectal cancer, with better protection of urinary and sexual functions. Highlights: Fascia propria of the rectum (FPR) and urogenital fascia (UGF) are two independent layers of fascia. The avascular plane between the FPR and UGF (i.e. visceral fascia) is the real 'holy plane'. Laparoscopic TME with UGF preservation is a feasible radical surgery for mid-low rectal cancer.